THE DEVELOPMENT OF FASHION AND ITS INFLUENCE OF LIFESTYLE TO PROVIDE INSPIRATION AND INSIGHTS IN TO MODERN CULTURE (Konferensiyalar | Conferences, 2024)
The general public's need for fashion is growing daily and has a significant impact on contemporary culture, despite the fact that it has been improving quickly over time. Not only do fashion designers showcase their yearly collections each season, but models, celebrities, and politicians all contribute significantly to elevating fashion to a public podium. As a result, how fashion develops nowadays has a big impact on people's interests in life, their personal growth, and their ability to work as demanding and competitive employees in the fashion industry. Fashion also reflects a person's culture and behaviour in both the corporate and social spheres. Information about them can be found in this article. People are inspired by fashion and are assisted in growing. The article, to put it briefly, discusses the evolution of fashion and how it has impacted contemporary culture. swiftly and effectively modify and reword your material.